2009
DOI: 10.1097/id.0b013e3181ad8e7a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Abutment Design on Clinical Status of Peri-Implant Tissues

Abstract: The differences in these mucogingival responses between these 2 groups at BL (during seating of abutments, especially of butt-joint abutments) and after 6-month loading indicated enhanced peri-implant soft tissue stability around the tapered abutments of this system. There was also enhanced-PTV in the test group for clinical mobility assessment after 6-month loading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…[23][24][25] Meanwhile, it was recognized that tapered abutments with platform switch increased peri-implant soft tissue stability compared to butt-joint abutments. 55,56 Although studies have compared the plaque and BOP index of soft tissues between abutments of different materials and different connection, the influence of abutment angle and height has not been researched so far. [55][56][57] Therefore, we analyzed the factors that might influence the peri-implant soft tissue health around the balanced base abutment with platform switch.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25] Meanwhile, it was recognized that tapered abutments with platform switch increased peri-implant soft tissue stability compared to butt-joint abutments. 55,56 Although studies have compared the plaque and BOP index of soft tissues between abutments of different materials and different connection, the influence of abutment angle and height has not been researched so far. [55][56][57] Therefore, we analyzed the factors that might influence the peri-implant soft tissue health around the balanced base abutment with platform switch.…”
Section: Discussionmentioning
confidence: 99%
“…55,56 Although studies have compared the plaque and BOP index of soft tissues between abutments of different materials and different connection, the influence of abutment angle and height has not been researched so far. [55][56][57] Therefore, we analyzed the factors that might influence the peri-implant soft tissue health around the balanced base abutment with platform switch. In our study, the short abutment showed more plaque risk than the long abutment while different angle abutments did not show significant influence on plaque or BOP index.…”
Section: Discussionmentioning
confidence: 99%
“…Bone-level implants restored with platform switching have less recession of soft tissues [110]. Soft tissues around tapered abutment recapitulated the physiologic dimensions of natural tooth and enhanced peri-implant soft tissue stability [111,112]. The peri-implant soft tissues and the marginal level of bone-toimplant contact were similar between self-tapping standard implants and Osseotite ® implants of the 3i Implant System with microtextured acid-etched surface [113].…”
Section: Effects Of Biological Width On Dental Implants Typesmentioning
confidence: 99%
“…The mucogingival response and Priotest values estimated after 3 and 6 months of observation pointed to ANKYLOS as a better system. 9 The process of osseointegration for implants with immediate prosthetic load was evaluated with an experimental study also in monkeys. ANKYLOS implants placed in the posterior part of the mandible and subjected to immediate loading became osseointegrated in a similar way as implants with delayed loading.…”
Section: Marginal Bone Loss Around Implants In Experimental Studies Imentioning
confidence: 99%